2023
DOI: 10.1186/s12933-023-02054-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of triglyceride glucose index with all-cause and cardiovascular mortality in the general population

Jiaqi Chen,
Kangxiang Wu,
Yiying Lin
et al.

Abstract: Objective The Triglyceride-glucose (TyG) index, a novel indicator of insulin resistance, has been associated with mortality from coronary artery diseases, ischemic stroke, and heart failure. In recent years, much emphasis has been placed on the relationship between the TyG index and mortality in the general population. However, the impact of age on the association between TyG and all-cause and cardiovascular mortality remains controversial. This study investigated the link between the TyG index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Patients aged < 24 years were excluded from the stratification analysis because only a small number developed IHD. Age categories (25–44, 45–64, and 65 and above) were selected based on previous cardiovascular epidemiological studies [ 29 , 30 ]. Health insurance premiums (categorized from 1 to 20) vary according to household income in Korea.…”
Section: Methodsmentioning
confidence: 99%
“…Patients aged < 24 years were excluded from the stratification analysis because only a small number developed IHD. Age categories (25–44, 45–64, and 65 and above) were selected based on previous cardiovascular epidemiological studies [ 29 , 30 ]. Health insurance premiums (categorized from 1 to 20) vary according to household income in Korea.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective cohort study has demonstrated a J shaped association between BMI and all cause mortality, which can be explained when the two different shapes in mortality risk for fat mass and lean body mass are taken together [35]. The NHANES has demonstrate a Non-linear trend in the relationships between TyG as well as TyG-WC indices with the all-cause mortality of MetS population [22]. This implies that these indices may have different mechanisms of action or interactions at different factors.…”
Section: /14mentioning
confidence: 99%
“…The China Health and Retirement Longitudinal Study (CHARLS) study found that TyG-BMI, TyG-WC, and TyG-WHtR performed better than BMI, WC, and WHtR in predicting MetS in middle-aged and early older adults (≥ 45 years of age) [20,21]. Currently, NHANES found that a non-linear trend between TyG index and TyG-WC indices with all-cause mortality of the MetS population in America [22]. Thus, additional research is necessary in different populations and ethnic group where the varieties of anthropometric and lipid measures especially the newly proposed indices have not been expansively analysed and studied.…”
mentioning
confidence: 99%
“…In addition, the triglyceride-glucose (TyG) index is easier to obtain than the HOMA-IR. The TyG index, which is based on fasting triglycerides and fasting glucose, has gained widespread acceptance as a reliable substitute indicator of IR in recent years for predicting CVD, DM, hypertension, stroke, and mortality [13][14][15][16]. Numerous studies have suggested that the diagnostic value of TyG for disease and IR is superior to that of the traditional indicator HOMA-IR [17][18][19].…”
Section: Introductionmentioning
confidence: 99%